Demand for safety and regional certification of food: Results from Great Britain and the Republic of Ireland. Issue 4 (1st April 2014) - Doherty, Edel; Campbell, Danny
Abstract : Purpose: – This paper aims to explore the relationship between consumer demand for enhanced food safety features and regional identification of food amongst consumers across Great Britain and the Republic of Ireland. Design/methodology/approach: – The paper uses the choice experiment method to determine preferences for food testing standards, traceability standards, health and welfare standards, region of origin and price. Findings: – The results show that substantial differences exist in preferences for the features between consumers in both countries. In addition, while stark differences are apparent between the two countries, in their preferences for food originating from their local region, the results suggest that consumers perceive significant substitutability between the enhanced safety features and the local regional label in both countries. Originality/value: – This paper provides a unique insight into preferences for a wide range of enhanced food safety features amongst consumers in these two countries. This is the first study to undertake a comparison of these countries using the choice experiment method. In addition, the paper provides a thorough overview of how consumers perceive the relationship between enhanced safety features and region of origin of food.